Human Rights and Democracy in Islamic Perspective - Busman Edyar; Ilda Hayati; Muslih Kondang (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to clarify Islamic perspectives on human rights and democracy. The research method employed is a literature study with a qualitative approach that is examined using content analysis. The results of the research show that, within certain limits, Islam upholds the implementation of human rights that must be obtained by everyone. In Islam, there are concepts of al-usia al-daruriyah (human needs) and al-usia al-hajjiyah (human interests) that humans must fulfill and defend, such as the right to life (hifz al-nafs), the right to religious freedom (hifz al-din), the right to free thought (hifz al-'aql), property rights (hifz al-mal), and the right to have offspring (hifz al-nasl). Likewise, with democracy, Islam upholds democratic principles such as al-musawah (egalitarianism), al-hurriyah (independence), al-ukhuwwah (brotherhood), al-Jadi (justice), and al-syura (deliberation). Even these principles are in line with the basic concepts of Islamic teachings to a certain extent, even though in practice, not all such democracies are justified. The parameters of democracy (including the concept of human rights) are that it is accepted by Islam as long as it does not contradict the essential principles of Islam.